Między autonomią a urzędniczymi wymaganiami. Praktyka działania tzw. ram kwalifikacji w wybranych uczelniach europejskich. Wybrane aspekty - Cyran, Karolina; Kurek-Ochmańska, Olga; Maj-Solarz, Dominika; Rozmus, Andrzej; Struck-Peregończyk, Monika (Wydawnictwo Naukowe UAM, 2015)
For several years Polish universities have operated in new conditions defined by the National Qualification Framework. When it comes to implementing the Qualification Framework, Ireland, the United Kingdom, Germany, and France are regarded as the model countries. Many solutions applied by those countries can be treated as examples of good practice. Surveys conducted at the above mentioned universities showed that the key to the universities’ teaching (and other) success is the appropriate balance between university autonomy and requirements of the regulatory institutions. In Poland there are autonomous universities on the one side and a great amount of clerical regulation caused by the implementation of the Qualification Framework on the other side. The experience of the surveyed universities from the United Kingdom, Ireland and Germany shows that the more freedom universities have in implementing the Qualification Framework, the more extensive the benefits.
Between Autonomy and Clerical Requirements. How the Qualification Framework Functions at Selected European Universities. Selected Aspects
Keywords: university autonomy; National Qualification Framework; teaching framework; higher education